Sistem Proteksi Generator Menggunakan Relai Differensial Unit 5-7 di PT. Indonesia Power PGU Suralaya - Dafiq Bimasakti; Bagus Dwicahyono (JURNAL TECNOSCIENZA, 2026)
Generators are important components in power generation systems and require protection systems to safeguard equipment from internal faults. One of the protection systems applied to Units 5–7 generators at PT Indonesia Power PGU Suralaya is the differential relay as the main protection system. This study aims to evaluate the setting parameters of the differential relay used in the generator protection system of Units 5–7 at PT Indonesia Power PGU Suralaya. The research employed a quantitative descriptive method with a case study approach. Data were collected during an industrial internship through observation, documentation, interviews, and literature review. The analyzed data included commissioning records, Current Transformer (CT) ratios, and differential relay setting parameters. The results indicate that the differential relay settings at Units 5, 6, and 7 have not changed from the original commissioning data. For relay 87G, the line CT and neutral CT ratios were 24000/5 A, with a differential current pickup (?I) of 125 mA and a slope setting of 10%. For relay 87GT, the UST A CT, USB B CT, and GEN CT ratios were 24000/5 A, while the GSU CT ratio was 1900/5 A, with a slope setting of 30%. The evaluation results show that the protection system configuration remains consistent with the initial commissioning settings. Therefore, the differential relay settings continue to meet the established protection parameters for generator protection in Units 5–7 at PT Indonesia Power PGU Suralaya.